Acidic extracellular pH promotes accumulation of free cholesterol in human monocyte-derived macrophages via inhibition of ACAT1 activity. (November 2020) - Lee-Rueckert, Miriam; Lappalainen, Jani; Leinonen, Hannele; Plihtari, Riia; Nordström, Tommy; Åkerman, Karl; Öörni, Katariina; Kovanen, Petri T.
Abstract: Background and aims: In focal areas of advanced human atherosclerotic lesions, the intimal fluid is acidic. An acidic medium impairs the ABCA1-mediated cholesterol efflux from macrophages, so tending to increase their content of free cholesterol, which is then available for esterification by the macrophage enzyme ACAT1. Here we investigated whether low extracellular pH would affect the activity of ACAT1. Methods: – Human monocyte-derived macrophages were first incubated with acetyl-LDL at neutral and acidic conditions (pH 7.5, 6.5, and 5.5) to generate foam cells, and then the foam cells were incubated with [ 3 H]oleate-BSA complexes, and the formation of [ 3 H]oleate-labeled cholesteryl esters was measured. ACAT1 activity was also measured in cell-free macrophage extracts. Results: – In acidic media, ACAT1-dependent cholesteryl [ 3 H]oleate generation became compromised in the developing foam cells and their content of free cholesterol increased. In line with this finding, ACAT1 activity in the soluble cell-free fraction derived from macrophage foam cells peaked at pH 7, and gradually decreased under acidic pH with a rapid drop below pH 6.5. Incubation of macrophages under progressively more acidic conditions (until pH 5.5) lowered the cytosolic pH of macrophages (down to pH 6.0). Such intracellular acidification did not affect macrophage gene expression of ACAT1 or the neutral CEH . Conclusions: Exposure of human macrophage foam cells to acidic conditions lowers their intracellular pH with simultaneous decrease in ACAT1 activity. This reduces cholesterol esterification and thus leads to accumulation of potentially toxic levels of free cholesterol, a contributing factor to macrophage foam cell death. Graphical abstract: Image 1 Highlights: In advancing atherosclerotic lesions the extracellular pH drops. Exposure of human macrophages to acidic culture media gradually leads to intracellular acidification. Cholesterol-esterifying acyl coenzyme A:cholesterol O-acyltransferase 1 (ACAT1) activity decreases in acidified macrophage foam cells. Decreased cholesterol esterification leads to accumulation of free cholesterol in the foam cells.